The invisible child: Sibling experiences of growing up with a brother with severe haemophilia—An interpretative phenomenological analysis. Issue 1 (18th December 2018) - Tregidgo, Catherine; Elander, James
Abstract : Introduction: Haemophilia is an inherited chronic condition that causes bleeding in the joints and soft tissue. Healthy siblings growing up in the family of a person with haemophilia can be affected socially and psychologically. Aim: To explore qualitatively the experiences of healthy siblings who grew up with a brother with severe haemophilia. Methods: Eleven healthy siblings (10 female, one male) who grew up with a brother with severe haemophilia A were recruited via the Haemophilia Society UK. The verbatim transcripts of individual semi‐structured interviews were analysed using interpretative phenomenological analysis (IPA). Results: Three themes were identified as follows: lack of parental attention, negative social emotions, and carrier status anxiety. Participants described having engaged in attention‐seeking behaviours because they felt they lacked parental attention. They also described the resentment, anger and frustration they felt about the effect their brothers' haemophilia had on their lives. Female participants described the impact their carrier status or lack of it had on their lives. Conclusion: These findings could be translated into better advocacy and support for siblings through haemophilia centres. More research is also needed on how healthy siblings are affected by haemophilia, including studies guided by family systems theory.